Cardiac Society of Nepal Consensus Recommendations for INR Monitoring and Warfarin Management - Joshi, Dikshya; Sharma, Apurb; Rajbanshi, Bijoy G.; Adhikari, Chandra Mani; Koirala, Raamesh; Bhattarai, Anil; Acharya, Anil; Nepal, Bipin; Sharma, Lucky; Thapa, Sanjeev; Pradhan, Sidhartha; Aryal, Marisha; et al. (Nepalese Heart Journal, 2026)
Background: Vitamin K antagonists (VKAs), particularly warfarin, remain the cornerstone of oral anticoagulation therapy in Nepal due to the high burden of rheumatic heart disease. Effective anticoagulation with VKAs requires meticulous monitoring of prothrombin time and international normalized ratio (PT/INR). However, significant variability exists in INR monitoring frequency, dose adjustment practices, laboratory standardization, and perioperative management across Nepal. Objective: To develop standardized, practical, and Nepal-specific consensus recommendations for PT/INR monitoring and warfarin management using a structured modified Delphi process. Methods: A three-round modified Delphi methodology was conducted among a multidisciplinary panel of clinicians involved in anticoagulation management in Nepal. Round 1 collected open-ended qualitative inputs to identify key thematic areas. In Round 2, structured consensus statements were developed and rated on a Likert scale. Statements with incomplete agreement were refined and re-evaluated in Round 3. Consensus thresholds were predefined, and recommendations were categorized accordingly. Results: Following three rounds of the modified Delphi process, 15 consensus recommendations were endorsed. Strong consensus was reached on recommendations related to therapeutic INR targets, dose-adjustment strategies, INR re-testing intervals, drug-drug interactions, perioperative management, and monitoring strategies for unstable patients. Consensus was not reached for select recommendations concerning routine reversal strategies in asymptomatic supratherapeutic INR and prolonged INR monitoring intervals. Final consensus recommendations addressed INR monitoring, warfarin management, and context-specific strategies for resource-limited and rural settings. Conclusion: This consensus provides a practical framework for PT/INR monitoring and warfarin management tailored to Nepal’s healthcare context. Adoption of these recommendations may help standardize practice, reduce preventable complications, and guide future research and policy development.